Main Issues of Qualified Economists Training in the Context of Digital Economy Development - Muhammedrizayevna, Tairova Masuma; Salimovna, Narzullayeva Gulchehra; ugliOybek, Juliboy; Furqatovna, Odinayeva Nigina (International Journal of Psychosocial Rehabilitation, 2020)
At the current stage of economic progress, innovative development of the economy has become an objective necessity. Today, while the importance of innovative and digital technologies in the economy is growing day by day, the issue of training qualified human resourcesis also getting one of the top priorities.This article focuses on the training of qualified economists in the context of the digital economy development. The article outlines the ongoing reforms in the education system and consistent measures to improve the quality of human resources. The article also highlights the importance and impact of training qualified economists. The priority directions of training qualified economists in the context of the development of the digital economy are highlighted.